Replicative aging in yeast involves dynamic intron retention patterns associated with mRNA processing/export and protein ubiquitination - Jesús Gómez-Montalvo; Alvaro de Obeso Fernández del Valle; Luis Fernando De la Cruz Gutiérrez; Jose Mario Gonzalez-Meljem; Christian Quintus Scheckhuber (Microbial Cell)
Saccharomyces cerevisiae (baker´s yeast) has yielded relevant in-sights into some of the basic mechanisms of organismal aging. Among these are genomic instability, oxidative stress, caloric restriction and mitochondrial dysfunction. Several genes are known to have an impact on the aging process, with corresponding mutants exhibiting short- or long-lived phenotypes. Re-search dedicated to unraveling the underlying cellular mechanisms can sup-port the identification of conserved mechanisms of aging in other species. One of the hitherto less studied fields in yeast aging is how the organism regulates its gene expression at the transcriptional level. To our knowledge, we present the first investigation into alternative splicing, particularly intron retention, during replicative aging of S. cerevisiae. This was achieved by utiliz-ing the IRFinder algorithm on a previously published RNA-seq data set by Janssens et al. (2015). In the present work, 44 differentially retained introns in 43 genes were identified during replicative aging. We found that genes with altered intron retention do not display significant changes in overall transcript levels. It was possible to functionally assign distinct groups of these genes to the cellular processes of mRNA processing and export (e.g., YRA1) in early and middle-aged yeast, and protein ubiquitination (e.g., UBC5) in older cells. In summary, our work uncovers a previously unexplored layer of the transcrip-tional program of yeast aging and, more generally, expands the knowledge on the occurrence of alternative splicing in baker´s yeast.